Retorika Etos Patos Logos dalam Ceramah Ustadz Hanan Attaki Tentang Mengingat Kematian - Nur Syavika; Rhani Febria (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to identify, describe, and dismantle in depth the utilization of rhetorical elements namely ethos (credibility), pathos (emotional appeal), and logos (logical reasoning) applied by Ustadz Hanan Attaki in his lecture on the importance of remembering death. The methodological foundation relies on a qualitative approach using qualitative content analysis to interpret the meanings, symbols, and rhetorical weight contained within the lecture text. Data collection was carried out through library research by reviewing relevant scientific literature and compiling a verbatim transcript from the video